Step-by-step explanation:
3x+8<4x−12
Move all terms containing x
to the left side of the inequality.
Tap for more steps...
−x+8<−12
Move all terms not containing x
−x<−20
x>20
Interval Notation:(20,∞)
Answer:
f(x)=5x^3-2x^2-90x-36=0
=x^2(5x-2)-18(5x-2)=(x^2-18)(5x-2)=0
x^2-18=0/5x-2=0
x^2=18=x=9√2
5x-2=0
x=2/5
zeros are 9√2,2/5
The required number is 19 given that -2 is added to a number, the sum is doubled and the result is -15 less than the number. This can be obtained by assuming the number as x, converting the given conditions to algebraic expression, forming algebraic equation and solving for x.
<h3>Find the required number:</h3>
Here in the question it is given that,
- The result is -15 less than the number
We have to find the required number.
Let the required number be x.
⇒ -2 is added to the number ⇒ -2 + x
⇒ the sum is doubled ⇒ 2(-2 + x)
⇒ the result is -15 less than the number ⇒ 2(-2 + x) = x -(-15)
2(-2 + x) = x + 15
⇒ - 4 + 2x = x + 15
⇒ x = 19
Hence the required number is 19 given that -2 is added to a number, the sum is doubled and the result is -15 less than the number.
Learn more about algebraic expression and equation here:
brainly.com/question/953809
#SPJ9
Answer:
![sin(\theta + \beta) = -\frac{\sqrt{7}}{5}-4\frac{\sqrt{2}}{15}](https://tex.z-dn.net/?f=sin%28%5Ctheta%20%2B%20%5Cbeta%29%20%3D%20-%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B5%7D-4%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B15%7D)
Step-by-step explanation:
step 1
Find the ![sin(\theta)](https://tex.z-dn.net/?f=sin%28%5Ctheta%29)
we know that
Applying the trigonometric identity
![sin^2(\theta)+ cos^2(\theta)=1](https://tex.z-dn.net/?f=sin%5E2%28%5Ctheta%29%2B%20cos%5E2%28%5Ctheta%29%3D1)
we have
![cos(\theta)=-\frac{\sqrt{2}}{3}](https://tex.z-dn.net/?f=cos%28%5Ctheta%29%3D-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B3%7D)
substitute
![sin^2(\theta)+ (-\frac{\sqrt{2}}{3})^2=1](https://tex.z-dn.net/?f=sin%5E2%28%5Ctheta%29%2B%20%28-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B3%7D%29%5E2%3D1)
![sin^2(\theta)+ \frac{2}{9}=1](https://tex.z-dn.net/?f=sin%5E2%28%5Ctheta%29%2B%20%5Cfrac%7B2%7D%7B9%7D%3D1)
![sin^2(\theta)=1- \frac{2}{9}](https://tex.z-dn.net/?f=sin%5E2%28%5Ctheta%29%3D1-%20%5Cfrac%7B2%7D%7B9%7D)
![sin^2(\theta)= \frac{7}{9}](https://tex.z-dn.net/?f=sin%5E2%28%5Ctheta%29%3D%20%5Cfrac%7B7%7D%7B9%7D)
![sin(\theta)=\pm\frac{\sqrt{7}}{3}](https://tex.z-dn.net/?f=sin%28%5Ctheta%29%3D%5Cpm%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B3%7D)
Remember that
π≤θ≤3π/2
so
Angle θ belong to the III Quadrant
That means ----> The sin(θ) is negative
![sin(\theta)=-\frac{\sqrt{7}}{3}](https://tex.z-dn.net/?f=sin%28%5Ctheta%29%3D-%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B3%7D)
step 2
Find the sec(β)
Applying the trigonometric identity
![tan^2(\beta)+1= sec^2(\beta)](https://tex.z-dn.net/?f=tan%5E2%28%5Cbeta%29%2B1%3D%20sec%5E2%28%5Cbeta%29)
we have
![tan(\beta)=\frac{4}{3}](https://tex.z-dn.net/?f=tan%28%5Cbeta%29%3D%5Cfrac%7B4%7D%7B3%7D)
substitute
![(\frac{4}{3})^2+1= sec^2(\beta)](https://tex.z-dn.net/?f=%28%5Cfrac%7B4%7D%7B3%7D%29%5E2%2B1%3D%20sec%5E2%28%5Cbeta%29)
![\frac{16}{9}+1= sec^2(\beta)](https://tex.z-dn.net/?f=%5Cfrac%7B16%7D%7B9%7D%2B1%3D%20sec%5E2%28%5Cbeta%29)
![sec^2(\beta)=\frac{25}{9}](https://tex.z-dn.net/?f=sec%5E2%28%5Cbeta%29%3D%5Cfrac%7B25%7D%7B9%7D)
![sec(\beta)=\pm\frac{5}{3}](https://tex.z-dn.net/?f=sec%28%5Cbeta%29%3D%5Cpm%5Cfrac%7B5%7D%7B3%7D)
we know
0≤β≤π/2 ----> II Quadrant
so
sec(β), sin(β) and cos(β) are positive
![sec(\beta)=\frac{5}{3}](https://tex.z-dn.net/?f=sec%28%5Cbeta%29%3D%5Cfrac%7B5%7D%7B3%7D)
Remember that
![sec(\beta)=\frac{1}{cos(\beta)}](https://tex.z-dn.net/?f=sec%28%5Cbeta%29%3D%5Cfrac%7B1%7D%7Bcos%28%5Cbeta%29%7D)
therefore
![cos(\beta)=\frac{3}{5}](https://tex.z-dn.net/?f=cos%28%5Cbeta%29%3D%5Cfrac%7B3%7D%7B5%7D)
step 3
Find the sin(β)
we know that
![tan(\beta)=\frac{sin(\beta)}{cos(\beta)}](https://tex.z-dn.net/?f=tan%28%5Cbeta%29%3D%5Cfrac%7Bsin%28%5Cbeta%29%7D%7Bcos%28%5Cbeta%29%7D)
we have
![tan(\beta)=\frac{4}{3}](https://tex.z-dn.net/?f=tan%28%5Cbeta%29%3D%5Cfrac%7B4%7D%7B3%7D)
![cos(\beta)=\frac{3}{5}](https://tex.z-dn.net/?f=cos%28%5Cbeta%29%3D%5Cfrac%7B3%7D%7B5%7D)
substitute
![(4/3)=\frac{sin(\beta)}{(3/5)}](https://tex.z-dn.net/?f=%284%2F3%29%3D%5Cfrac%7Bsin%28%5Cbeta%29%7D%7B%283%2F5%29%7D)
therefore
![sin(\beta)=\frac{4}{5}](https://tex.z-dn.net/?f=sin%28%5Cbeta%29%3D%5Cfrac%7B4%7D%7B5%7D)
step 4
Find sin(θ+β)
we know that
![sin(A + B) = sin A cos B + cos A sin B](https://tex.z-dn.net/?f=sin%28A%20%2B%20B%29%20%3D%20sin%20A%20cos%20B%20%2B%20cos%20A%20sin%20B)
so
In this problem
![sin(\theta + \beta) = sin(\theta)cos(\beta)+ cos(\theta)sin (\beta)](https://tex.z-dn.net/?f=sin%28%5Ctheta%20%2B%20%5Cbeta%29%20%3D%20sin%28%5Ctheta%29cos%28%5Cbeta%29%2B%20cos%28%5Ctheta%29sin%20%28%5Cbeta%29)
we have
![sin(\theta)=-\frac{\sqrt{7}}{3}](https://tex.z-dn.net/?f=sin%28%5Ctheta%29%3D-%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B3%7D)
![cos(\theta)=-\frac{\sqrt{2}}{3}](https://tex.z-dn.net/?f=cos%28%5Ctheta%29%3D-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B3%7D)
![sin(\beta)=\frac{4}{5}](https://tex.z-dn.net/?f=sin%28%5Cbeta%29%3D%5Cfrac%7B4%7D%7B5%7D)
![cos(\beta)=\frac{3}{5}](https://tex.z-dn.net/?f=cos%28%5Cbeta%29%3D%5Cfrac%7B3%7D%7B5%7D)
substitute the given values in the formula
![sin(\theta + \beta) = (-\frac{\sqrt{7}}{3})(\frac{3}{5})+ (-\frac{\sqrt{2}}{3})(\frac{4}{5})](https://tex.z-dn.net/?f=sin%28%5Ctheta%20%2B%20%5Cbeta%29%20%3D%20%28-%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B3%7D%29%28%5Cfrac%7B3%7D%7B5%7D%29%2B%20%28-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B3%7D%29%28%5Cfrac%7B4%7D%7B5%7D%29)
![sin(\theta + \beta) = (-3\frac{\sqrt{7}}{15})+ (-4\frac{\sqrt{2}}{15})](https://tex.z-dn.net/?f=sin%28%5Ctheta%20%2B%20%5Cbeta%29%20%3D%20%28-3%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B15%7D%29%2B%20%28-4%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B15%7D%29)
![sin(\theta + \beta) = -\frac{\sqrt{7}}{5}-4\frac{\sqrt{2}}{15}](https://tex.z-dn.net/?f=sin%28%5Ctheta%20%2B%20%5Cbeta%29%20%3D%20-%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B5%7D-4%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B15%7D)
3/5 cup of fruit because 1/3 +1/3 +1/3 = 3/3 or one. 1/5 +1/5 +1/5 = 3/5